The influence of magnesium and manganese cations on the chemical and bioactive properties of purple and green basil - de Oliveira, Izamara; Chrysargyris, Antonios; Finimundy, Tiane C.; Carocho, Márcio; Santos-Buelga, Celestino; Calhelha, Ricardo C.; Tzortzakis, Nikos G.; Barros, Lillian; Heleno, Sandrina A (My University, 2024)
This research investigated the effects of hydroponic cultivation with enriched concentrations of magnesium (+Mg), manganese (+Mn), a combination of +Mg and +Mn, or decreased concentrations of these minerals (control) on the nutritional, chemical, and bioactive attributes of purple and green basil. While Mn significantly increased the growth of purple basil and affected the composition of essential oil and mineral accumulation, plants treated with Mg showed alterations in nutrient absorption. Protein values were lower, indicating suboptimal protein synthesis, but significant increases were observed in fat, ash, and carbohydrates, suggesting a more nutrient-rich composition due to hydroponic cultivation. Regarding phenolic compounds, green basil showed higher concentrations of rosmarinic acid with +Mg+Mn, while purple basil exhibited lower levels with the addition of +Mn or +Mg+Mn. Antioxidant activities mirrored the phenolic profile, with purple basil displaying superior performance in the thiobarbituric acid-reactive substance (TBARS) test with +Mg treatment, and green basil showing higher activity in the cell antioxidant activity (CAA) test with the +Mg+Mn combination. In microbiological analyses, purple basil was more effective against S. aureus, while green basil performed better against L. monocytogenes. Although none were bactericidal, all treatments showed potential as antimicrobials. Purple basil extracts had significant antiproliferative effects on tumor cell lines, especially non-small cell lung carcinoma (NCI-H460), with synergistic effects observed in gastric adenocarcinoma (AGS) with +Mg+Mn. Additionally, +Mg+Mn demonstrated unique efficacy against colorectal adenocarcinoma (CaCo2) and breast carcinoma (MFC-7 cells), without toxicity to non-tumor a renal epithelial cell line from an African green monkey (VERO) cell, emphasizing the safety of the extracts. Green basil extracts showed no activity against the tumor cell lines analyzed (AGS, Caco2, MFC-7 and NCI-H460); however, they revealed remarkable antiproliferative effects against NCI-H460 cells in the control group. The results are important because they show how mineral treatments, such as the use of magnesium and manganese, influence the nutritional and medicinal properties of purple and green basil leaves. This highlights the relevance of manipulating nutrient solutions to improve plant quality, which is crucial for the production of functional foods and dietary supplements.
Keywords: Animals; Antioxidants; Cations; Cell Line; Tumor; Humans